Aktivitas Seni dan Keterampilan Tangan (Craft) Sebagai Upaya Menumbuhkan Jiwa Entrepreneurship Komunitas Ibu Rumah Tangga - Meilawaty, Okta; Widati, Titiani; Amiany, Amiany; Gus Two Four, Selasten (Diteksi : Jurnal Pengabdian Kepada Masyarakat, 2024)
Bukit Tunggal Ward is one of crowded settlements where the residents mostly working in informal and other non-formal sectors. The existence of creative craft industries along with training and assistance can be a solution for growing entrepreneurship to this area resident, to increase the economic conditions in the area, and also can help in improving families economic conditions in Bukit Tunggal Ward. To increase income and the economy, it is necessary to provide skills in the form of creative crafts (craft) industry which is carried out through training using counseling methods, training and direct practice of handicraft arts (craft). It is hoped that this activity can be a solution in an effort to foster an entrepreneurial spirit and improve the economy of the area, as well as being able to meet the needs and improve the economy of the families of the Bukit Tunggal Ward. Data collection was carried out through field studies, namely collecting data directly in the field by conducting interviews with the Head of RT.02/RW.03, Palangka Village. The data obtained was analyzed simply and the community of housewives living in Bukit Tunggal Ward was selected. Craft activities consist of: (1) preparation, observation; (2) location sourvey and coordinations; (3) socialization and assistance; and (4) evaluation. The results of the training are crafted handbag, wallet and gift bag. Craft activities consist of: (1) preparation, observation; (2) location sourvey and coordinations; (3) socialization and assistance; and (4) evaluation. The results of the training are crafted handbag, wallet and gift bag. The activity hopefully have begin a positive movement in the local community which can influence the communitities in Palangka Raya and Kalimantan Tengah as a whole, as the craft activities can be a possibility to increase the community’s welfare.